Wool fibre quality in Danish prehistoric textiles: A 3,000 year survey - Skals, Irene; Mannering, Ulla; Strand, Eva Andersson (Archaeological Textiles Review, 2024)
During the last 15 years analyses by fibre diameter measurements of a wide range of yarn samples from Danish archaeological wool textiles dated from the Early Bronze to the Viking Ages (circa 1800 BCE to 1050 CE) have been made. The extraordinary preservation of these textiles makes them ideal for interpretations regarding wool fibre development and processing. The aim of this paper is to investigate possible changes in fibre quality through time that can be related to either differences in the raw wool or in the work process preparing the wool for spinning. The standard statistical calculations of the wool fibre diameters which form the basis for classifying prehistoric wool have been used but slightly elaborated to extract more detailed information and facilitate the interpretation of the collected data. The fibre qualities in the textiles from the different archaeological periods have been compared and the principles for wool development and processing assessed for each. The results have revealed that a similar kind of wool was used for a long period of time in the Danish area with only minor changes that could indicate adjustments of the production and processing to meet the demands for textile appearance. Further, the results show that a change took place in the textile fibre quality between circa 400 CE and 600 CE which indicates the introduction of a different sheep breed and processing strategy.